Path of a deaf teacher: autobiography and relationship with educational policies (Olhar de Professor, 2024)
This article derives from a master’s study in education, which research is an autobiographical account based on the life story of a deaf individual. It examines how inclusive education policies have influenced his experiences. The objectives are: a) understanding the epistemological perspectives of autobiographical research; b) exploring the concepts of identity and culture, and the historical context of inclusive educational policies in Brazil; c) assessing how inclusive educational policies have impacted the dimensions of a deaf individual’s life. The research methodology employed is the autobiographical approach, which is based on valuing personal experience and reflecting on this experience. The narratives were constructed and reconstructed. Reassessing how sign language and natural language were perceived, respectively, was crucial, as well as conducting a new analysis on subjectivity and deafness.
Keywords: Autobiographical research; Deaf identity; Inclusive educational policies